The Problem Of The Color Line: Spatial Access To Hospital Services For Minoritized Racial And Ethnic Groups - Eberth, Jan M; Hung, Peiyin; Benavidez, Gabriel A; Probst, Janice C; Zahnd, Whitney E; McNatt, Mary-Katherine; Toussaint, Ebony; Merrell, Melinda A; Crouch, Elizabeth; Oyesode, Oyeleye J; Yell, Nicholas (Health affairs (Millwood, Va.), 2022)
Examining how spatial access to health care varies across geography is key to documenting structural inequalities in the United States. In this article and the accompanying StoryMap, our team identified ZIP Code Tabulation Areas (ZCTAs) with the largest share of minoritized racial and ethnic populations and measured distances to the nearest hospital offering emergency services, trauma care, obstetrics, outpatient surgery, intensive care, and cardiac care. In rural areas, ZCTAs with high Black or American Indian/Alaska Native representation were significantly farther from services than ZCTAs with high White representation. The opposite was true for urban ZCTAs, with high White ZCTAs being farther from most services. These patterns likely result from a combination of housing policies that restrict housing opportunities and federal health policies that are based on service provision rather than community need. The findings also illustrate the difficulty of using a single metric-distance-to investigate access to care on a national scale.